1998
DOI: 10.1086/517442
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Repeated Gonococcal Infections: San Francisco, 1990–1992

Abstract: Gonococcal (GC) infections are very common and are sustained by a core group of persons who often have repeated GC infections. Identifying individual risk factors for repeated GC infection is essential so that infection control programs can develop better strategies for decreasing the incidence of GC infection. A case-control study among high-risk persons found that being African American, having previous chlamydia infection, and having less than a high-school education were associated with repeated GC infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…In our cohort, syphilis reinfection accounted for three quarters of incident syphilis cases as indicated by baseline reactive titers and appropriate increase of titers reflective of new infection. This supports the idea that there is a higher risk core group of “repeaters” who are reinfected with syphilis [11, 18]. This calls for focused prevention of syphilis beyond periodic testing among high-risk individuals.…”
Section: Discussionsupporting
confidence: 72%
“…In our cohort, syphilis reinfection accounted for three quarters of incident syphilis cases as indicated by baseline reactive titers and appropriate increase of titers reflective of new infection. This supports the idea that there is a higher risk core group of “repeaters” who are reinfected with syphilis [11, 18]. This calls for focused prevention of syphilis beyond periodic testing among high-risk individuals.…”
Section: Discussionsupporting
confidence: 72%
“…6,7,18,21,28,31,51,52,56 In the 2 prospective studies, an African-American partner was associated with STI acquisition 6,7 In cross-sectional studies, Black or African-American race was positively associated with MG, 18,28 GC, 21 repeat GC 56 and composite STI measures. 31,52 One study reported an African-American partner was significantly associated with GC and CT among White and “Other” males and females, but not among African-Americans.…”
Section: Resultsmentioning
confidence: 98%
“…Ten 6,7,18,21,28,30,31,51,52,56 of 11 6,7,18,21,26,28,30,31,51,52,56 studies which investigated race/ethnicity were US-based; 9 of the 10 reported significant findings. 6,7,18,21,28,31,51,52,56 In the 2 prospective studies, an African-American partner was associated with STI acquisition 6,7 In cross-sectional studies, Black or African-American race was positively associated with MG, 18,28 GC, 21 repeat GC 56 and composite STI measures.…”
Section: Resultsmentioning
confidence: 99%
“…Because the focus of the analysis was repeat infection rather than treatment failure, antibiotic efficacy studies, which generally have short-term follow-up, were not included in our analysis. Twenty-three studies were excluded because reinfection rates were not stratified by sex [11][12][13][14][15][16][17][18][19][20][21] or specific etiology (chlamydia or gonorrhea), 13,14,[21][22][23][24] the publication was a nonpeer-reviewed letter, 25 data were duplicative of already published material, 26 -28 reinfection rates could not be calculated using the data provided, 29 -32 or initial infection was not laboratory-confirmed. 33 Specific study design, proportion of females retested, diagnostic test type used, length of follow-up, geographic region, and population demographics were not considered in the inclusion and exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%